Influence of fine motor skills in the prewriting process of the Initial Level. Sublevel 2 - Guzmán Pinto, Rosa Alexandra; López Vaca, Wilman Luis (Revista Ecos de la Academia, 2024)
The development of fine motor skills at the beginning level is essential to acquire adequate writing skills. The purpose of this research was to diagnose the influence of fine motor skills for the development of prewriting, which was carried out on 55 students of Initial Education, sublevel 2 of the Millennium Educational Unit “Jatun Kuraka Otavalo”. To analyze the study variables, tests and a graphic motor observation sheet were applied. Likewise, the degree of correlation between the variables was established to be able to verify how fine motor skills influence the prewriting process. The methodology based on direct observation of the sample was used and its results were analyzed through descriptive and correlational procedures. The results obtained determine that of the 55 children to whom the subtest was administered, only 20 were able to thread the needle and 23 could draw 9 or more parts of the body, which indicates that there are fine motor problems. From the correlational analysis it is established that the fine motor variable correlates mostly with the prewriting variables.